Marketing Strategy for Islamic People's Financing Bank (BPRS) Products at PT BPRS Puduarta Insani - Amelia Azura; Ahmad Amin Dalimunthe (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Marketing Strategy is a strategy or fundamental approach taken by companies in completing advertising activities. Before formulating a company strategy, it is necessary to have a plan or a goal to be achieved. The rapid development in the banking world requires Islamic banks that are present in the midst of conventional banks to be able to survive and compete and continue to improve competencies in order to attract customer trust and interest in the quality of products and services available at these Islamic banks. With the increasing interest of customers to switch to Islamic banks, it will certainly increase the achievement of sales targets for the products offered. The research was conducted to determine the marketing strategy in achieving the target at..PT. BPRS..Puduarta..Insani.